Friday

April 18, 2014

April 18, 2014

Posted by **Anonymous** on Saturday, March 29, 2008 at 4:47pm.

Find (f o g)(-6) when f(x)=4x+4 and g(x)=6x^2-3x-6.

I originally came up with 918, but the answer is 916. Obviously I was close, but could someone tell how to get 916. I am studying for a test and am re-working my homwork problems. Thanks.

- Algebra -
**Anonymous**, Saturday, March 29, 2008 at 5:44pmSet your problem up

-6=4x=4 -6=6^2-3x-6

work these out

- Algebra -
**Damon**, Saturday, March 29, 2008 at 6:12pmg(-6) = 6*36 - 3*(-6) -6

= 228

f(228) = 4(228)+4

=912 +4 = 916

**Related Questions**

Pre-algebra - Could someone please help me solve the following problems, and ...

Math - Can someone please check my answers below for accurateness? The ...

Algebra - I am confused by this problem. Solve: Clear fractions or decimal first...

algebra - solve (4x^2+2x-4) - (x^2-5x-4)= I came up with 3x^2+7 is my answer ...

algebra - simplify (6x^3-16x^2+11x-5)/(3x-2) (3x-2)(2x-1)^2-3 my muliple choice ...

PreCalculus - I'm trying to find the x-intercepts of a polynomial function = 4x^...

Math/Algebra - Find each sum or difference (3x^2 + 7x- 2)+ (2x^2 - 3x + 4) ...

algebra - solve by the subtitution method. 2x+3y=8 -6x+y=36 I came up with (-2,-...

Algebra......Help Quick!! - 12a^3bc-18a^2bc^2+6a^2c, x^2+20x+36, 12x^4-8x^3-4x^2...

Pre-algebra - I have some practice problems, and I need to have them worked out...